Modelling of layout design and selection of appropriate design with a case study. (2017) - Abbasi, Ebrahim; Ahmadi, Seyed Hosein; Naderi, Saeed; Vahdani, Farhad Abbasgholivand
Facility location problem (FLP) is a subject that deals with arrangement of different departments in working environment. An efficient location design will lead to amelioration in performance efficiency, effective use of spaces, and reduction in logistics costs. Accordingly, it is considered as a strategic problem, which has a significant influence on the performance of production system. That is why companies try to assess and reassess their current layout designs, and try to plan a proper layout design for their production and service departments. In this regard, this paper presents a mathematical model for selecting a proper layout design. Current paper concerns with facility layout design based on mathematical model. Considering special features of each department and the relation of activities between every one of them, the most significant model was selected. Then, according to the departments' special features and by means of mathematical model the departments were located in a two-dimension space thru CPLEX 12. In this way the initial solution of location problem was attained. The results reflect that the observed hospital did not make a good use of the available space and that there was too much empty space which could be used for building new rooms and providing more accessibility among departments.